Lagenorhynchus obliquidens Gill 1865 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
5. Pacific White-sided Dolphin Lagenorhynchus obliquidens French: Dauphin de Gill / German: Pazifik-Wei 3seitendelfin / Spanish: Delfin de flancos blancos del Pacifico Other common names: Hook-finned Porpoise, Pacific Striped Porpoise, Pacific White-striped Dolphin Taxonomy. Lagenorhynchus obliquidens Gill, 1865, “obtained at San Francisco, California,” USA. Taxonomy of Lagenorhynchus is currently in dispute; recent molecular analyses have revealed that the genus is not monophyletic. L. obliquidens and L. obscurus may form a sister lineage to Cephalorhynchus. The genus Sagmatias has been suggested as an alternative classification. Geographical forms may be distinguished by body length and skull characteristics; there are two forms in the eastern North Pacific Ocean and two forms in the western Pacific Ocean. Coastal populations seem to be genetically and morphologically distinct from offshore populations. Monotypic. Distribution. Cool temperate waters of the N Pacific, primarily between 38° N and 47° N, including the Yellow Sea, Sea ofJapan, S Sea of Okhotsk, S Bering Sea, and S Gulf of California. Descriptive notes. Total length 240-250 cm (males) and 230-240 cm (females); weight c.198 kg. Neonates are 92-100 cm long. The Pacific White-sided Dolphin has stocky body-shape with short, well-defined beak. Flippers are large and falcate with slightly rounded tips. Dorsal fin is also large and falcate, and in older males, it may be very hooked at tip, which is slightly rounded. Belly, lowerjaw and throat are white and bordered by a black band. Sides and back are black with several pale-gray patches. These patches include streaks around lower melon,streakjust above beak and eyes that may merge with larger gray patches on lower anterior flanks, wide pale-gray patches along posterior margin of dorsal fin, and wide lateral gray streak along tailstock that may diverge into one or two wispy stripes along upper mid-body below dorsal fin. Beak, flippers, and flukes are dark gray to black, but flippers may have paler patches ...